اهمية نبات البردي في حياة المصريين القدماء - بورني,دليلة (University of Eloued جامعة الوادي, 2024)
نبات البردي من أقدم النباتات التي تعرض لها الانسان بالتسجيل و الشرح خاصة المصريين القدماء ، و ذلك منذ اكتشافهم مزايا و فوائد هذا النبات و في وقت مبكر من التاريخ، فاستخدموا البردي في أغلب متطلبات حياتهم، فنجدهم قد استخلصوا من الجزء الرخو الموجود في أسفل الساق طعاما شعبيا، و من الجزء الباقي من الساق صنعوا الكثير من الأدوات المتصلة بحياتهم، مثل الصناديق، و المناضد ، و السلال و الحصير و أشرعة الزوارق، كما صنعوا من لبه النعال التي كان الكهان يرتدونها، و من السيقان الجافة التي تربط حزما متجاورة صنعوا المراكب الصغيرة التي استخدموها في صيد الطيور و الأسماك خاصة في مياه المستنقعات و البرك، كما لفوا ألياف البردي لصناعة الحبال المقاومة لتأثير المياه. الواقع أن أهم استخدام لنبات البردي هو صناعة الورق التي استخدمت في الكتابة و التدوين، فدخل مجال الإنتاج و الاحتكار إذ أصبح البردي مادة اقتصادية هائلة. فقاموا بزراعته و الاعتناء به.Papyrus is one of the oldest plants that man has been exposed to through recording and explanation, especially the ancient Egyptians, since they discovered the benefits and benefits of this plant from ancient times , so they used papyrus in most of their vital needs. From the rest of the stems, the Egyptians made many tools related to their daily life, such as boxes, tables, ropes, mats and sails for boats, and from its pulp they made the sandals that carried the priests, and from the dry stems which bind the adjacent sheaves they made small boats which they used to hunt birds and fish, especially in swamps and ponds, and they also wrapped sedge fibers to make the ropes resistant to the impact of water. In fact, the most important use of the papyrus plant is the paper industry, which has been used in writing and inscription. It has entered the field of production and monopoly, as papyrus has become a huge economical material. They planted it and took care of it.
Keywords: مصر القديمة; نبات البردي; البردية; رق البردي; Egypt civilization; writing; papyrus; Ancient Egyptians; invention